Prediction of mechanical behavior of cartilaginous infant hips in pavlik harness: A subject‐specific simulation study on normal and dysplastic hips - Vafaeian, Behzad; Adeeb, Samer; El‐Rich, Marwan; Dulai, Sukhdeep K.; Jaremko, Jacob L. (Journal of orthopaedic research, 2019)
ABSTRACT In dysplastic infant hips undergoing abduction harness treatment, cartilage contact pressure is believed to have a role in therapeutic cartilage remodeling and also in the complication of femoral head avascular necrosis. To improve our understanding of the role of contact pressure in the remodeling and the complication, we modeled cartilage contact pressure in cartilaginous infant hips undergoing Pavlik harness treatment. In subject‐specific finite element modeling, we simulated contact pressure of normal and dysplastic hips in Pavlik harness at 90° flexion and gravity‐induced abduction angles of 40°, 60° and 80°. We demonstrated that morphologies of acetabulum and femoral head both affected contact pressure distributions. The simulations showed that in Pavlik harness, contact pressure was mainly distributed along anterior and posterior acetabulum, leaving the acetabular roof only lightly loaded (normal hip) or unloaded (dysplastic hip). From a mechanobiological perspective, these conditions may contribute to therapeutic remodeling of the joint in Pavlik harness. Furthermore, contact pressure increased with the angle of abduction, until at the extreme abduction angle (80°), the lateral femoral head also contacted the posterior acetabular edge. Contact pressure in this area could contribute to femoral head avascular necrosis by reducing flow in femoral head blood vessels. The contact pressure we simulated can plausibly account for both the therapeutic effects and main adverse effect of abduction harness treatment for developmental dysplasia of the hip. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res